Atrial fibrillation in β-thalassemia Major Patients: Diagnosis, Management and Therapeutic Options. (4th May 2018) - Barbero, Umberto; Fornari, Federico; Guarguagli, Silvia; Gaglioti, Carmen Maria; Longo, Filomena; Doronzo, Baldassarre; Anselmino, Matteo; Piga, Antonio
Abstract: The prevalence of atrial fibrillation (AFib) in β-thalassemia major (β-TM) patients has increased in the last few years, reaching up to 33.0%. Several factors may drive this value to even more in the next few years. We summarized the main challenges in the management and therapy of AFib in this very specific group of patients.